Technical Precision as the Guardian of Governance: The Independent Roles of Budget Accuracy and Enterprise Risk Management in Mitigating Budgetary Slack - Donny Arif Kurniawan; Masiyah Kholmi (Arkus, 2025)
In the complex governance landscape of state-owned enterprises (SOEs), budgetary slack represents a significant agency cost that undermines public resource efficiency. While behavioral determinants of slack are well-documented, the mitigating roles of technical budget quality and formalized risk controls remain under-explored in emerging markets. Adopting a quantitative explanatory design, this study collected data from 50 key personnel, including management accountants, risk officers, and internal auditors, across five subsidiaries of a prominent Indonesian Marine Service SOE. To address the sample size limitation, a post-hoc G*Power analysis (alpha = 0.05, Power = 0.99) confirmed sufficient sensitivity for the observed effect sizes. Data were analyzed using structural equation modeling (SEM-PLS) with a full collinearity assessment to rule out common method bias. The empirical analysis reveals that budget accuracy (p = 0.014, f-square = 0.32) and risk management (p = 0.022, f-square = 0.28) exert a significant negative influence on budgetary slack. Conversely, budget clarity and evaluation demonstrated no significant effect. Crucially, risk management did not moderate the relationship between budget quality and slack (p > 0.05), functioning instead as a powerful, independent determinant. In conclusion, reducing slack in SOEs relies less on soft goal clarity and more on the ex-ante precision of financial estimates and the parallel integration of risk protocols. SOEs are advised to transition from historical-based budgeting to driver-based forecasting models to reduce information asymmetry.